Clinical utilities of aromatase inhibitors in breast cancer - Chumsri S (Dove Medical Press, 2015)
Saranya Chumsri Department of Hematology and Oncology, Mayo Clinic, Jacksonville, FL, USA Abstract: Aromatase is an enzyme that converts testosterones to estrogens. Inhibition of this enzyme has been shown to have several clinical utilities in breast cancer. Currently, there are three aromatase inhibitors (AIs) in clinical use, namely anastrozole, letrozole, and exemestane. AIs have been used in various clinical settings for breast cancer, ranging from chemoprevention in breast cancer to treating breast cancer in both early stage in the adjuvant setting and metastatic disease. This article reviews mechanism of action, AI classification, and clinical utilities of AIs in various clinical settings in the context of breast cancer. Keywords: aromatase inhibitor, endocrine therapy, breast cancer